A Overview of Mother's Knowledge About Baby Massage at Helen Tarigan Clinic in 2022 - Merlina Sinabariba; Besty Mangunsong; Ermawaty Arisandi (Science Midwifery, 2022)
Background: Baby massage is a health treatment in the form of touch therapy with certain techniques given to babies so that touch and therapy stimuli can be achieved.The purpose of giving massage to babies is to release endorphins so that it gives a sense of relaxation to the baby's muscles which will make the baby more comfortable and comfortable safe communication between mother and baby . Research Methods: This type of research is descriptive. The sampling technique was accidental sampling. The location of this research is at the Helen Tarigan Clinic in 2022 May 2022. With 30 respondents the measuring instrument used is a closed, closed questionnaire which is tested for validity with a frequency distribution . 5 respondents (16.7%), with sufficient knowledge 13 respondents (43.3%), with less knowledge 12 respondents (40%). Conclusion : Based on the results of the study, it shows that most or the majority of respondents have sufficient knowledge (43.3%). Suggestions It is hoped that after knowing the results of this study, researchers can add knowledge, experience and apply midwifery science which includes knowledge about infant massage.